Selected multicriteria shortest path problems: An analysis of complexity, models and adaptation of standard algorithms - Tarapata, Zbigniew (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents selected multicriteria (multiobjective) approaches to shortest path problems. A classification of multiobjective shortest path (MOSP) problems is given. Different models of MOSP problems are discussed in detail. Methods of solving the formulated optimization problems are presented.
Keywords: multiobjective shortest path; stochastic shortest path; algorithm complexity; routing problem; terrain-based